Effect of Auxin ( IBA ) in rooting cutting four varieties of pomegranate and improve some vegetative and roots characteristics - التميمي, حارث محمود عزيز (Journal of Kerbala for Agricultural Sciences, 2015)
The experiment was conducted in a privet nursery in Husseiniya township / Karbala city for the period from mid-February until mid-July. to study the effect of different concentrations of the IBA on the percentage cutting rooted four varieties of pomegranate (Salimi and Hloo and Khadrawi and Wonderful) and speed up the formation of shoots and root and reduce the period of their stay in the nursery. Three IBA concentrations were used (0, 2000 and 4000 mg.L-1 ). Randomized complete Block Design (R.C.B.D) was used with three replicates and 5 cuttings for each replicates. The result showed that cuttings treated with IBA at a concentration of (4000 mg.L-1) increased, significantly the rooting percentage, number and length of roots and dry weight of roots, shoots length, number leaves and dry weight of vegetative comparing with other concentrations. The results showed also superiority variety Salimi significantly on the other varieties in the most vegetative characteristics and roots. the varieties different in their responsiveness of the IBA, where superiority cultivar Salimi and treatment concentration (4000 mg.L-1) significantly to give the highest rate of characteristics studied, followed by the product was Hloo.